Decompositions of edge-colored digraphs : a new technique in the construction of constant-weight codes and related families - Chee, Yeow Meng (2019)
We demonstrate that certain Johnson-type bounds are asymptotically exact for a variety of classes of codes, namely, constant-composition codes, nonbinary constant-weight codes, group divisible codes, and multiply constant-weight codes. We achieve this via an application of the theory of decomposition of edge-colored digraphs.